Translation of Value-Semantic Narratives in Public Digital Communication: Opportunities and Limitations - Albina B. Romashkina; Daria A. Kirichuk (RUDN Journal of Political Science)
The study is devoted to the role of public digital communication in the processes of formation and translation of value-semantic narratives in modern political communication. The authors consider the importance of the axiological space of the state in the management of public and individual consciousness. It is determined that Internet communication and digital algorithms contribute to the formation of a variety of agendas and discourses, which are influenced not only by the state, but also by new subjects of political communication - “digital elites”, bloggers and other users who form public digital communication, including from abroad. Traditional agents of socialization cannot fully shape a person’s worldview, and therefore citizens may be more susceptible to manipulative algorithmic tools of digital platforms on which destructive narratives are broadcast that contribute to the destruction of the worldview and values of society. Therefore, in order to preserve the sovereignty of the state and to resist a new type of colonialism based on the technological advantages of Western countries, it is necessary to ensure information, technological and cultural security, which will also protect the integral axiological space necessary for the consolidation of society.